Farmer Learning Event, Lower Nyando - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Over 500 farmers in lower Nyando are testing a portfolio of promising climate risk management, adaptation and mitigation interventions in partnership with the Ministry of Agriculture, Livestock, and Fisheries, the Ministry of Environment, Water and Natural Resources, the Kenya Agricultural Research Institute, World Neighbors, Vi Agroforestry, the World Agroforestry Centre, and local community based organizations. The experience is helping participants gradually make changes to their farming practices. A few are taking the lead, and in June hosted their neighbors on their farms for a learning event that brought people together for learning and cross-fertilization in lower Nyando. Photos: V. Atakos (CCAFS) and P. Kimeli (CCAFS)